2018
DOI: 10.1097/01.naj.0000541440.91369.00
|View full text |Cite
|
Sign up to set email alerts
|

Making It Stick: Developing and Testing the Difficult Intravenous Access (DIVA) Tool

Abstract: The DIVA tool gave novice nurses a reliable indication of the probable difficulty of an IV insertion and resulted in a change in the IV policy standard at the institution, which now limits the number of peripheral IV insertion attempts to two per nurse and four per patient, bringing current policy into alignment with the 2016 Infusion Therapy Standards of Practice. Use of the revised and validated DIVA tool has the potential to enhance patient comfort and satisfaction and effect significant change in nursing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 14 publications
1
31
0
2
Order By: Relevance
“…55 As for the vascular access conditions, a previous history of DPIVC, as well as vein conditions of visibility and palpability, resulted to be statistically significant in most of the studies in which they were included, 38À41 which constitute a pool of relevant variables that can be easily applicable in clinical practice to detect patients at risk even before the first attempt of cannulation. 56 Together with these, clinician or professional-related variables need to be included in future studies and explored with more precision. Professional expertise in cannulation technique seem to be associated, not with a higher success of the technique, but with a more accurate capacity to predict difficulty based on the assessment of the vessel previous to puncture.…”
Section: Discussionmentioning
confidence: 99%
“…55 As for the vascular access conditions, a previous history of DPIVC, as well as vein conditions of visibility and palpability, resulted to be statistically significant in most of the studies in which they were included, 38À41 which constitute a pool of relevant variables that can be easily applicable in clinical practice to detect patients at risk even before the first attempt of cannulation. 56 Together with these, clinician or professional-related variables need to be included in future studies and explored with more precision. Professional expertise in cannulation technique seem to be associated, not with a higher success of the technique, but with a more accurate capacity to predict difficulty based on the assessment of the vessel previous to puncture.…”
Section: Discussionmentioning
confidence: 99%
“…Complete view of the needle (CVN) was accomplished in 41.7% of procedures, while partial view of the needle (PVN) occurred in 42% of procedures (Figs. 4,5,6). Repositioning the needle/guidewire (RNG) was necessary for successful UGVC in 49% of procedures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Central vessel cannulation entails more difficulties in paediatric patients than in adult ones, and is not devoid of risks or complications. Obtaining vein access in paediatric patients may be a challenge for both medical and nursing staff [1][2][3][4][5][6]. Great advances were achieved using ultrasoundbased guidance [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The updated UK VHP 2020 framework now incorporates consideration of patients with difficult intravenous access (DIVA) and the need to identify these patients at the earliest opportunity (Smith-Ehrhardt et al, 2018;van Loon et al, 2019). Van Loon et al (2019) found that even the most experienced healthcare staff undertaking cannulation on a regular basis experienced difficulty in cannulation, with a failure rate up to 19% on the first attempt.…”
Section: Vein Assessmentmentioning
confidence: 99%